Efektivitas Kinerja Pembelajaran Online (E-Learning) di Era New Normal - Pricylia Chintya Dewi Buntuang; Erdiyansyah Erdiyansyah (Journal on Education, 2023)
The World Health Organization has declared Covid-19 as a pandemic that has posed a contemporary threat to humanity. This pandemic has successfully forced global shutdown of several activities, including educational activities, and this has resulted in tremendous crisis-response migration of universities with online learning serving as the educational platform. This study aims to determine the effectiveness of online learning (e-learning) performance in the new normal era in the learning process at Tadulako University. The population of this study were lecturers and students at Tadulako University, while the sampling was carried out simply randomly it is means the entire population has the opportunity to be sampled. Source of data in this research comes from primary data and secondary data. Data collection techniques through observation, interviews, and documentation. Data analysis was carried out interactively. The results of the study concluded that the higher education management at Tadulako University was mostly not ready to adopt an e-learning educational approach as an alternative to teaching and learning during COVID-19. This study also identified e-learning packages that were mostly adopted (WhatsApp forum, Zoom meeting, Google Classroom, Learning Management System, and Webinar) by institutions during COVID-19. The majority of staff and students do not agree to have easy access to computers. Staff and students also indicated their training needs on the use of the e-learning platform.